The Effect of SEKAR (Sumber Edukasi Anemia yang Relevan) Card-Based Nutrition Education on Knowledge and Iron Intake in Pregnant Women - Saibatul Hairiyah; Aminah Toaha; Nur Abri; Dini Indo Virawati (Journal of Health and Nutrition Research, 2023)
Anemia in pregnant women is one of the most common public health emergencies, especially in low- and middle-income countries, such as Indonesia. This study aims to determine the effect of SEKAR (Sumber Edukasi Anemia yang Relevan) card-based nutrition education on knowledge and iron intake in pregnant women at the Mangkupalas Samarinda Health Center. The type of research used is an experimental study with a pre-test and post-test research design with the control group. A total of 36 pregnant women were taken into samples divided into 2 groups, namely 18 interventions and 18 controls based on inclusion and exclusion criteria.  Nutrition education variables were obtained using SEKAR cards and leaflets containing information about anemia. The knowledge was obtained using a structured questionnaire that had been validated and a pregnant woman's iron intake was obtained using a 24-hour in-depth food recall interview. Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results show that the effect of nutrition education using SEKAR on the knowledge of pregnant women (p = 0.003), and iron intake (p = 0.031). Leaflet media did not affect knowledge (p = 0.072) and iron intake (p = 0.078). There was a significant difference between SEKAR cards and leaflets on knowledge improvement (p = 0.001) and there was no significant difference between the use of SEKAR card media and leaflets on iron intake (p = 0.516). Media SEKAR is superior and effective was used in this study. It is hoped that there will be continuous nutrition education